Marek Thee: My Story A Journey through the 20th Century - Thee, Marek; Gleditsch, Nils Petter; Tønnesson, Stein; Erdal, Marta Bivand (SpringerBriefs on Pioneers in Science and Practice, 2023)
Marek Thee was a Jewish Polish journalist, scholar, and activist. This book tells his life from narrowly escaping death in the Holocaust to exile in Palestine, where he became attached to the Polish consular service. On his return to Poland in 1950, he worked for the Foreign Ministry and later for the Polish Institute for International Affairs. He served as Head of the Polish delegation to the International Control Commission in Indochina in the late 1950s. In 1968 he lost his job and his Polish citizenship in a nationalistic and antisemitic campaign. He was able to move to Norway where he worked for twenty years at the Peace Research Institute Oslo (PRIO), editing an international quarterly journal, Bulletin of Peace Proposals and doing research on the arms race. In retirement, he continued his research and writing at the Norwegian Human Rights Institute. The book vividly relates the drama of his life in Poland, Palestine, Indochina, and Norway. This is an open access book.